Emerging Role of COL10A1 in Breast Cancer Pathogenesis and its Potential as a Clinical Biomarker - Roy, Nilima Rani; Narju, Suraiya Pervin; Hoque, Farzana; Barman, Sanchita (Journal of Rangpur Medical College, 2026)
Background: Breast cancer is a leading malignancy worldwide, with high morbidity and mortality among women. Despite advances in therapy, metastasis, recurrence, and resistance remain challenges. Collagen type X alpha-1 (COL10A1) is normally expressed in cartilage but is increasingly implicated in tumorigenesis. Overexpression of COL10A1 in breast cancer correlates with higher grade, invasiveness, and poor prognosis. Objective: To evaluate COL10A1 expression in breast cancer and its association with tumor characteristics, receptor status, and potential biomarker utility. Methods: A hospital-based cross-sectional study was conducted at department of Surgery, Dhaka Medical College Hospital from July 2022 to June 2023, including 40 breast cancer patients. Data on demographics, clinical features, and reproductive history were collected, and tissue samples were analyzed for COL10A1 expression. Inclusion required histopathological confirmed breast cancer in women _40 years. Statistical analysis used SPSS for frequencies, percentages, means, and chi-square tests. Ethical approval and informed consent were obtained, ensuring confidentiality and voluntary participation. Results: The study of 40 breast cancer patients revealed a mean age of 47.41 years. The majority had invasive ductal carcinoma (70%), Grade II (50%) or III (35%) tumors, and hormone-sensitive disease (60% ER-positive, 50% PR-positive). HER2-positivity was 25%. Critically, 80% exhibited moderate-to-high COL10A1 expression, which was strongly associated with high-grade tumors, as 10 of 14 Grade III patients showed high expression. Conclusion: COL10A1 overexpression correlates with aggressive breast cancer, highlighting its potential as a prognostic biomarker. J Rang Med Col.2026 Mar;11(1): 105-110